2002
DOI: 10.14712/18059694.2019.78
|View full text |Cite
|
Sign up to set email alerts
|

Yellow Nail Syndrome or Diffuse Lymphatic Network Disease

Abstract: We report a man aged 68 years old with pneumothorax and chronic bilateral pleural effusion in association with a history of yellow nails. The diagnosis of yellow nail syndrome based on yellow nails, lymphedema, chronic pleural effusion and intestinal lymphangiectasia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2005
2005
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 13 publications
0
4
0
Order By: Relevance
“…‘Yellow nail syndrome’ is a well recognized although uncommon condition of nail dystrophy associated with lymphoedema 42 . The primary pathology is thought to be lymphatic dysfunction, but the cause for the underlying nail dystrophy is poorly understood 43–45 . Further work in this field may reveal more about this condition and shed light on the higher prevalence of nail disease found in other causes of lymphoedema such as LF.…”
Section: Discussionmentioning
confidence: 99%
“…‘Yellow nail syndrome’ is a well recognized although uncommon condition of nail dystrophy associated with lymphoedema 42 . The primary pathology is thought to be lymphatic dysfunction, but the cause for the underlying nail dystrophy is poorly understood 43–45 . Further work in this field may reveal more about this condition and shed light on the higher prevalence of nail disease found in other causes of lymphoedema such as LF.…”
Section: Discussionmentioning
confidence: 99%
“…Comprehensive literature review revealed intestinal lymphangiectasia is rarely reported in patients > 65 years old, and nearly all cases in the elderly occurred in intestinal lymphangiectasia secondary to Waldenstrom macroglobulinemia, [ 26 ] or genetic syndromes. [ 27 ] This case appears to be the oldest reported case of PIL, with another case reported in a 73-year-old patient. [ 28 ] This report extends the maximal age of presentation of PIL; this old age is notable because PIL generally presents in infants as a presumed congenital defect.…”
Section: Discussionmentioning
confidence: 90%
“…One hundred and twelve studies involving 150 patients were selected for review, spanning a period of nearly 50 years. Figure presents a flow chart for the complete breakdown in the identification of appropriate studies . They all corresponded to the description of isolated case reports (between 1 and 4 per item) and a retrospective series of 19 patients…”
Section: Resultsmentioning
confidence: 99%